A protein–polymer hybrid gene carrier based on thermophilic histone and polyethylenimine1. (24th September 2015) - Shi, Hui; Han, Haobo; Xing, Zhen; Chen, Jiawen; Wang, Yudi; Zhang, Aijun; Shi, Wei; Li, Quanshun
<x xml:space="preserve">Abstract</x> Protein–polymer hybrid gene carrier with high transfection efficiency and low cytotoxicity.